New Image Encryption Based on Pixel Mixing and Generating Chaos System - mohaimen Hassan; Alaa Kadhim (Al-Qadisiyah Journal of Pure Science, 2020)
There was suggested new utilizing of the dispersion principle, based on the Lorenz Map, and chaos theory is known as perfect for using cryptography applications for their properties like unpredictability and sensitive initial states as one of the complex encryption approaches. to disengage the color of pixels (R, G, B). Was created this suggest with mixing all each color pixel to swap horizontally, vertically, or diagonally, finally using XOR operation. only milliseconds to encryption and decryption image, because the behavior of block cipher that leads to the period for the image to be decrypted fairly close as the images. The experiments demonstrate that the information security capabilities will be both safe more efficient, the result of our analysis of picture quality evaluation, differential attacks (NPSR), (UACI), Pixels correlation shows the quality and strength of encryption processing, Entropy show good results and closely to 8.